A METHODOLOGY FOR DETERMINING RISKS BASED ON THE ANALYSIS OF INJURIES TO EMPLOYEES OF INDUSTRIAL ENTERPRISES - Petrenko, I.; Chencheva, O.; Zozulia, S.; Shevchenko, V.; Lohvinkov, S. (Municipal economy of cities. Series: «Economy science», 2024)
The article aims to analyse the causes of occupational injuries, identify risk factors for employees, and improve workplace safety and accident prevention standards. To achieve the stated aim, the authors applied a comprehensive approach, which included an in-depth study of recent injury trends, identification of the main causal factors, and a thorough examination of the risks affecting working conditions and leading to injuries. The research methodology included a variety of tools, such as a deep analysis of statistical data on injuries in the context of an industrial enterprise, a review of internal documentation, and an evaluation of risk factors. The study results provided a detailed picture of the changing trajectory of injuries among industrial workers, which is closely related to their length of service and experience at the enterprise. Based on this understanding, we derived a specific risk assessment formula that synthesised the relationship between injuries and length of service. In addition, a thorough analysis of the structure of injuries during different shifts revealed a pronounced tendency for accidents to occur in the evening and at night, partly due to the psychological and physiological stress experienced by employees during these periods and the impact of microclimatic working conditions. To enhance the effectiveness of the risk assessment methodology, we proposed to integrate a comfort factor coefficient that shows the microclimatic factors’ impact on occupational safety and injury rates. These efforts have resulted in an improved risk assessment formula that can provide a more accurate prognosis of injury incidents and help optimise occupational health and safety protocols for employees at industrial enterprises. In addition, using statistical data, the study determined the cause-effect relation between risks to industrial workers, shown through the visual representation of an Ishikawa diagram, thus providing a further perspective for risk assessment in the enterprise.